2020
DOI: 10.1016/j.arth.2020.01.039
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bladder Catheterization Technique on Postoperative Urinary Tract Infections After Primary Total Hip Arthroplasty

Abstract: Background: Urinary bladder catheters are potential sources of infection after total hip arthroplasty (THA). Therefore, the goal of this study was to determine if intermittent catheterization provides a decreased risk of postoperative urinary tract infections (UTIs) compared with indwelling catheterization in THA patients. Methods: Patients undergoing THA at 15 hospitals within a large health system were prospectively collected between 2017 and 2019 and then stratified based on catheterization technique: no-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…found indwelling catheterization to be associated with a lower rate of POUR with no effect on the rate of postoperative UTI in a cohort of patients undergoing both THA and total knee arthroplasty [ 14 ]. This is in contrast to Garbarino et al., who identified indwelling urinary catheterization as an independent risk factor for UTI in a retrospective review of over 7300 patients undergoing primary THA [ 15 ]. When considering primary THA performed under spinal anesthesia specifically, a randomized controlled trial of 200 patients by Miller et al.…”
Section: Discussioncontrasting
confidence: 58%
“…found indwelling catheterization to be associated with a lower rate of POUR with no effect on the rate of postoperative UTI in a cohort of patients undergoing both THA and total knee arthroplasty [ 14 ]. This is in contrast to Garbarino et al., who identified indwelling urinary catheterization as an independent risk factor for UTI in a retrospective review of over 7300 patients undergoing primary THA [ 15 ]. When considering primary THA performed under spinal anesthesia specifically, a randomized controlled trial of 200 patients by Miller et al.…”
Section: Discussioncontrasting
confidence: 58%
“…Multiple recent studies have demonstrated a notable association between increasing age and the development of POUR. 4-6,8,17,18 This contrasts with a study by Bracey et al 10 that found no association between age and POUR. Male sex has also been linked to the development of POUR in multiple studies, although one prospective cohort study found no association between the two.…”
Section: Patient Risk Factorsmentioning
confidence: 71%
“…3 In addition, POUR is associated with increased rates of urinary tract infection; 5% to 22% of the patients undergoing catheterization develop a subsequent urinary tract infection, which is accompanied by an increased risk for periprosthetic joint infection. 4,5 Although POUR is not a new phenomenon, the advent of modern rapid recovery TJA with an emphasis on same-day or next-day patient discharge has highlighted the importance of appropriately mitigating its occurrence. The objective of this review was to synthesize the recent literature on POUR in the setting of TJA: discussing incidence, predisposing risk factors, scoring assessments for risk stratification, prevention strategies, and treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, catheters have also been associated with UTI [21][22][23] . The incidence of catheter-associated UTI increases the longer a catheter remains in place 24 , which is concerning as UTIs have been associated with the development of periprosthetic joint infections (PJIs) [25][26][27] . Therefore, catheter use to mitigate POUR is controversial.…”
mentioning
confidence: 99%